PENGEMBANGAN DESAIN LKPD DIGITAL IPAS BERMUATAN CODING AI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KOMPUTASIONAL SISWA KELAS 5 SD - Putra, M. Andiki Ramadhan Firdaus; Ramadhan, Gilang Mas; Layyinah, Rahmatika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a Digital Student Worksheet (LKPD) design model for Science and Social Studies (IPAS) based on Artificial Intelligence (AI) coding to enhance the computational thinking skills of fifth-grade elementary school students. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. The research participants included subject matter experts, media experts, teachers, and fifth-grade students. Data were collected through observations, interviews, validation questionnaires, response questionnaires, and computational thinking tests. The data were analyzed using descriptive quantitative techniques and the N-Gain formula to measure improvements in learning outcomes. The findings indicate that the developed Digital LKPD met the validity criteria based on evaluations by subject matter and media experts, received positive responses from teachers and students, and effectively improved students' computational thinking skills, as evidenced by higher post-test scores than pre-test scores. Therefore, the AI coding-based Digital IPAS LKPD is considered feasible as an innovative learning medium to support IPAS instruction while fostering elementary school students' computational thinking skills.